POLICY OF APPLICATION OF THE LEGISLATION IN THE SPHERE OF RENDERING MEDICAL CARE FOR MINOR - I. M. Vilgonenko; N. Y. Belokopytova; I. V. Kosenko (Современная наука и инновации)
Modern development of medicine and new technologies dictate the need to reform the legislation regulating the protection of medical rights of both minors and their parents (guardians, Trustees, legal representatives).